Effect of body mass on kinetic and perceptual variables during basketball maneuvers in shoes of different midsole hardness - Nin, Darren Zijie (2014)
The purpose of this study was to investigate the effects of body mass and shoe midsole hardness on kinetic and perceptual variables during the performance of three movements which were (i) layup, (ii) shot-blocking and (iii) drop landing (0.42 m). Thirty male university basketball players were divided into ‘heavy’ (n = 15, body mass = 82.7 ± 4.3 kg) or ‘light’ (n = 15, 63.1 ± 2.8 kg) groups according to their body mass. Each participant performed five trials of each movement in each shoe condition (soft, medium or hard). Vertical ground reaction force (VGRF) during landing was sampled simultaneously using multiple wood-top force plates. Perceptual responses on five parameters (forefoot cushioning, rear foot cushioning, forefoot stability, rear foot stability and overall comfort) were measured after each test condition using a 150 mm Visual Analogue Scale (VAS). A two-way 2 x 3 (body mass x shoe) mixed factorial analysis of variance (ANOVA) was performed on each kinetic and perception variable. No interaction effects between group and shoe conditions were found for kinetic and perceptual variables. Rear foot loading rate in heavy group was higher (p=.014) than light group during layup first step. For both groups: rear foot loading rate in hard shoe was higher (p=.011) than soft shoe during layup first step; forefoot peak VGRF in soft shoe was higher (p=.011) than hard shoe during shot-block. Perception of cushioning was consistent with shoe hardness across tasks.